Impact of tobacco smoking on oral microbiota – a case-control study. - Hattan, Abdulrahman Ali; Hattan, Essa Ali; Alqahtani, Abdulaziz Maree; Alqutaym, Omar Saud; Alqahtani, Refdan Obeid; Alzahrani, Khaled Ghormallah; Al-Otaibi, Abdulrahman Abdullah; Aldwsari, Omar Mufi; Alkhathlan, Khalid Mansour; Aldossari, Mohammed Abdullah (Medicni Perspektivi, 2018)
Oral microbiota is a vital part of human microbiota, including bacterial, protozoa, viral and fungal species. Beneficial microbes form biofilms to form a first-line defense against harmful microorganisms. Tobacco smoking is considered a major environmental factor affecting the orodental microbiota. Smokers harbor more pathogenic microbes than non-smokers. In fact, cigarette smoking exposes the oral cavity to a large number of toxicants, perturbing the oral microbial ecology through various mechanisms. In Saudi Arabia, research on the impact of tobacco smoking on oral microbiota is still lacking. Therefore, this case-control study is an important addition to the literature in terms of tobacco use and its effects on oral microbiota and oral hygiene. 130 men were recruited for this study, including 65 smokers and 65 non-smokers. The following parameters were recorded for all 130 participants – age, weight, height and education. The aim of this study was to investigate and compare the effect of tobacco smoking on the oral microbiome of smokers and non-smokers. The majority of the smokers were young adults between the ages of 21 and 30 inclusive (n=27). The results show that excessive microorganism growth was seen in smokers to a greater degree than non-smokers (38.5% of smokers vs. 8.8% of non-smokers). Not surprisingly, a significant majority (85.3%) of non-smokers had moderate microorganism growth compared to only 53.8% of smokers. cigarette smoking facilitates excessive growth of oral microorganisms, predisposing smokers to various periodontal diseases. In fact, smoking perturbs the balance of oral microbiota, producing a viable environment for microbes to cause diseases. Further large scale prospective studies are required to determine the exact mechanism that causes tobacco to affect oral microbiota.